Case of paradoxical adverse response to mepolizumab with mepolizumab-induced alopecia in severe eosinophilic asthma. Issue 2 (20th February 2020) - Nixon, Rodanthe; Despiney, Raquel; Pfeffer, Paul
Abstract : Recent years have seen an increase in use of mepolizumab and other biological therapies for the treatment of severe eosinophilic asthma. A few cases of paradoxical responses to mepolizumab therapy have now been reported and are hypothesised as being a response to immune complex formation. We present a case of mepolizumab-induced alopecia in a patient with paradoxical adverse response to mepolizumab given for severe eosinophilic asthma. We postulate this could be secondary to autoimmune mechanisms and that it could help herald poor response to treatment, thereby facilitating early identification of patients having paradoxical responses.